Estudo por espectroscopia de RMN e cálculos teóricos de derivados da norcânfora e de ditianos - Bandoch, Gisele de Freitas Gauze (2008)
The present work reports the study of the mains parameters of NMR spectroscopy in norcamphor and dithiane derivatives. In the first part the results of synthesis, separation and purification of 3-exo-hidroxinorcânfora e 3-exo e 3-endo-metiltio e metilselenonorcânforas are being presented as well as the complete assignment of 1H and 13C NMR signals. The compounds structures were optimized through Density Functional Theory (DFT), by B3LYP method. The observed 1H chemical shifts were compared with the corresponding calculated value using the CHARGE and Gaussian programs. Good agreement between the experimental and both sets of calculated values was observed, with the version parameterized of CHARGE program being more accurate, mainly for the protons in around of the functional groups. This data illustrates the utility of CHARGE program for the chemical shifts assignment and also as a tool for the elucidation of chemical structures. The second part of this work reports the study of sulfur oxidation influence on 2JHH e 1JCH coupling constants and consequently, of the orbital interactions, in 1,3 and 1,4dithiane sulfoxides and sulfones. In addition, were analyzed the factors governing the conformational behavior of these compounds. The compounds geometries were optimized at the MP2/cc-pVDZ level. The conformational equilibrium and the orbital interactions were analyzed using experiments NMR data and theoretical calculations by NBO theory. The conformational preference for the 1,3 and 1,4-dithiane sulfoxides and sulfones are determined by balance between two factor, delocalization interaction (attractive) and steric interaction (repulsive). The coupling constants were calculated with the Gaussian 03 program, using distinct methods (B3LYP, B971 and PBEPBE). The NBO calculations were used to determine of orbital interactions effects on coupling constants. The results showed that the hyperconjugative interactions have a great influence on 2JHH e 1JCH coupling constants values and can be used to explain the different coupling values in a molecular system.